MASSIVE SAND BEDS ATTRIBUTED TO DEPOSITION BY DENSE WATER CASCADES IN THE BOURCART CANYON HEAD, GULF OF LIONS (NORTHWESTERN MEDITERRANEAN SEA) - Gaudin M.; Jouanneau J.M.; Mulder T.; Cirac P.; Berné S.; Palanques A.; Puig P.; Rabineau M.; Imbert P. (My University, 2006)
Nowadays, the Gulf of Lions continental shelf and slope are under the influence of dense water cascading, wind-induced bottom currents and the geostrophic Northern Current. In order to characterize sedimentary activity at the shelf break, several interface and piston cores were taken in the Bourcart canyon head and a current meter equipped with temperature, conductivity, pressure and turbidity sensors was moored during the 2003-2004 winter season. Even if the canyon is not connected directly to continental sources since Last Glacial Maximum, detailed grain size, X-ray and sediment facies analysis of interface cores show that down to 350 m water depth, the canyon head is blanketed by up to 1.5 m of structureless muddy medium-grained sand. 210Pbexc activity measurements demonstrate present day sedimentary activity of the canyon head. Time series of currents with peak velocity reaching 0.37 m/s, suspended sediment concentration and temperature indicate that dense water cascading is the main process allowing the reworking, transport and accumulation of sand within the canyon head, even though winter 2003-2004 was characterized by low cascading events compared to other years. These sand beds, called "cascadite" constitute a new type of deposit that differs from other typical slope deposits (turbidites, hyperpycnites, contourites) in terms of flow duration and sedimentological characteristics. They are similar to shallow water contourites. They might be time-equivalent to the recent turbidites described throughout the deep western Gulf of Lions basin. © 2006 Elsevier B.V. All rights reserved.
Keywords: 210PBEXC ACTIVITY; CASCADING; SAND DEPOSITS; SUBMARINE CANYON